Debris flow [electronic resource] : mechanics, prediction and countermeasures - Takahashi, Tamotsu , 1939- (Balkema-proceedings and monographs in engineering, water and earth sciences, 2007)
This is a comprehensive account to the subject and treats both the theoretical and applied aspects of debris flow. In the first part, the fundamental mechanical aspects are discussed, like flow characteristics, type classification, mechanics, occurrence and development, fully developed flow and deposition processes. The second part sheds light on the application of the theories presented in computer simulated reproductions of some real disasters. Special attention is paid to debris flow controlling structures, design effectiveness and performance, soft countermeasure problems, like the id.